The power of images and forces of fragments in the works of Pier Paolo Vergerio the Elder - Špikić, Marko (Array, 2006)
Article deals with the perception of antiquities in the works of italian humanist Pier Paolo Vergerio the Elder. At the beginning of the 15th Century he was one of the founders of the humanist project of discovery of classical antiquity. Author is discussing three Vergerio's texts: a letter on the distruction of Vergil's statue in Mantua from 1397, a letter on Roman antiquities from 1398 and treatise De ingenuis moribus from the beginning of the 15th Century. Vergerio is presented as a predecessor of the antiquarian studies in the European Renaissance culture.